The Role of the Innate Immune System in ALS - Phani, Sudarshan; Re, Diane B.; Przedborski, Serge (Frontiers in Pharmacology, 2012)
Amyotrophic lateral sclerosis (ALS) is a fatal, adult-onset neurodegenerative disease that is characterized by the death of upper and lower motor neurons. Recent studies have made it clear that although motor neurons are the primary targets of the degenerative process, other cell types play key roles in the death of motor neurons. Most notably, cells of the immune system, including astrocytes and microglia have come under increasing scrutiny, after multiple lines of evidence have shown these cells to be deleterious to motor neurons. Both in vitro and in vivo experiments have shown that astrocytes and microglia containing mutated SOD1 are harmful to motor neurons. Several studies on ALS and other neurodegenerative diseases have revealed that reactive astrocytes and microglia are capable of releasing pro-inflammatory factors such as cytokines and chemokines, which are harmful to neighboring neurons. In addition, it is believed that diseased astrocytes can specifically kill motor neurons through the release of toxic factors. Furthermore, in an animal model of the disease, it has been shown that the reduction of SOD1 in microglia may be able to slow the progression of ALS symptoms. Although the exact pathways of motor neuron death in ALS have yet to be elucidated, studies have suggested that they die through aBax-dependent signaling pathway. Mounting evidence suggests that neuroinflammation plays an important role in the degeneration of motor neurons. Based on these findings, anti-inflammatory compounds are currently being tested for their potential to reduce disease severity; however, these studies are only in the preliminary stages. While we understand that astrocytes and microglia play a role in the death of motor neurons in ALS, much work needs to be done to fully understand ALS pathology and the role the immune system plays in disease onset and progression.